Plan educativo para la prevención del consumo de drogas y alcohol en adolescentes del centro de salud venus, 2023. - Elizalde Bravo, Ximena Alexandra (2025)
Drug and alcohol use among adolescents is a high-risk problem worldwide, impacting their physical and mental health, as well as their social and educational environment. In this context, an educational plan was designed to prevent the consumption of these substances at the Venus Health Center in 2023, using a quasi-experimental methodology that included the participation of 16 adolescents between 10 and 19 years old. Through surveys, it was found that, although adolescents had basic knowledge about the harmful effects of drug and alcohol use, many were unaware of their long-term consequences and associated psychological effects. The use of the Assist Test, an instrument validated by the WHO, was essential to assess adolescents' involvement with psychoactive substances, identifying consumption patterns and facilitating early detection of problems. In addition, risk factors such as peer pressure and lack of recreational activities were identified, underlining the need to reinforce preventive education through educational talks and informational materials. Open communication and active parental involvement were found to be essential for prevention, highlighting the importance of training families and the community in health communication and education strategies. The proposed educational plan provided guidance on access to health services and addressed the lack of psychological support, although its effectiveness was limited. However, valuable data was collected and strategies were developed that foster a safe and open dialogue environment. The success of the plan depends on the collaboration between adolescents, parents and educators, working together to adapt it to the changing needs of young people, with a proactive approach that can generate a positive impact on their well-being and comprehensive development.